Tax competition in Europe: Europe in competition with other world regions? - Frank Streif (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Corporate tax levels have fallen substantially in Europe during the last decades. A broad literature has identified tax competition as one reason for this decline in corporate tax levels. However, none of these studies explicitly asks the question whether tax competition within regions is different from tax competition across regions, e.g. due to global regionalism of foreign direct investments. This is a crucial question to answer in order to discuss the desirability of tax harmonization in a distinct region, for example, within the European Union. Therefore, the study aims to give hints on the question whether the decline in corporate tax levels in Europe is mainly driven by tax competition between EU member states or by pressure from other world regions. The results of this study, which makes use of tax reaction functions, indicate that there is evidence for tax competition within Europe, whereas there is no robust evidence that European countries compete with countries from other world regions.
urn:nbn:de:bsz:180-madoc-401776
Keywords: H2; H77; H87; 330; corporate taxes; tax competition; tax harmonization; Europe